1998
DOI: 10.1121/1.421115
|View full text |Cite
|
Sign up to set email alerts
|

Sound radiation by various types of laboratory breaking waves in fresh and salt water

Abstract: A recent article [A. R. Kolaini and L. A. Crum, J. Acoust. Soc. Am. 96, 1755–1765 (1994)] reported the measurements of the ambient sound generated by laboratory breaking waves over the range 100–20 000 Hz in fresh water. Those observations from both spilling- and plunging-type breakers have been repeated in the same manner and wavemaker/anechoic tank with water that had 25‰ salt in its content. The observations in salt water, just like those in fresh water, reveal that the sources of sound in laboratory spilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Results for chords larger than 3 mm are not shown for clarity. Present bubble size measurements highlighted similar trends as bubble size observations by KOLAINI (1998) andORRIS andNICHOLAS (2000). First, we observed a drastically lesser number of bubble chords smaller than 0.6 and 0.3 mm in freshwater and seawater, respectively ( Figure 7).…”
Section: Comparison Between Different Water Solutionssupporting
confidence: 68%
See 1 more Smart Citation
“…Results for chords larger than 3 mm are not shown for clarity. Present bubble size measurements highlighted similar trends as bubble size observations by KOLAINI (1998) andORRIS andNICHOLAS (2000). First, we observed a drastically lesser number of bubble chords smaller than 0.6 and 0.3 mm in freshwater and seawater, respectively ( Figure 7).…”
Section: Comparison Between Different Water Solutionssupporting
confidence: 68%
“…Past studies often relied upon photographic and video techniques that are restricted to low air volume fractions (Table 1). Recently, acoustic techniques were introduced (e.g., DEANE, 1997;KOLAINI, 1998;PHELPS and LEIGHTON, 1998), but the transformation from acoustic signature to bubble sizes must account for turbulent shear and interactions between bubbles of different sizes (CHANSON and MANASSEH, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed experiment on this topic is reported in Lamarre (1993) and Kolaini (1998). Lamarre (1993) found that immediately beneath breaking waves a high air volumetric concentration can be recorded within the first metre of the surface, equivalent to up to 24% in the ocean (which is several orders of magnitude higher than the time-averaged values reported by other authors, e.g.…”
Section: The Effect Of Air Entrapmentmentioning
confidence: 52%
“…The bubble size population was measured by Kolaini (1998) through a high-speed video camera with fibre optic cables.…”
Section: Measurements Techniques In the Surf And Swash Areamentioning
confidence: 99%
“…The advantages of laboratory measurements have been used numerous times to investigate sound generation by waves made to break via dispersive focusing. [1][2][3][4][5] The dispersive focusing mechanism is fundamentally different than that of shoaling, which can also be easily reproduced in a laboratory environment. Although a number of field measurements have been reported (e.g., Deane 6 ), to date, sound generation by shoaling breakers has not been extensively studied within the laboratory.…”
Section: Introductionmentioning
confidence: 99%